A bioactive porous scaffold containing collagen/ phosphorous-modified polycaprolactone for osteogenesis of adipose-derived mesenchymal stem cells. (15th May 2022) - Safari, Banafsheh; Aghazadeh, Marziyeh; Roshangar, Leila; Aghanejad, Ayuob; Davaran, Soodabeh
Graphical abstract: Highlights: A collagen-based bioactive porous biopolymer was synthesized and characterized. A collagen/phosphorous-modified polycaprolactone scaffold was fabricated and utilized for osteogenesis of mesenchymal stem cells. The scaffold can support proper cell attachment and promote cell proliferation. Abstract: A biocompatible scaffold with appropriate physicochemical properties and efficient biological performance is the main component of bone tissue engineering. Here, we report the fabrication of collagen/P-PCL, a bioactive hybrid scaffold containing collagen and phosphorus-modified polycaprolactone (P-PCL). The phosphorylated polymer was synthesized and characterized by FT-IR spectroscopy. Porous scaffold prepared by mixing and cross-linking collagen and P-PCL solution, followed by freeze-drying method. The obtained hybrid scaffold was characterized by FT-IR and its morphology was observed by SEM. Density, porosity, swelling ratio, mechanical behavior, and degradability of the scaffold were assessed. Finally, biological responses of Adipose-derived Mesenchymal Stem Cells (AD-MSCs) seeded on the scaffold were evaluated. MTT assay revealed that the scaffold could be considered biocompatible. The scaffold was osteoconductive and efficiently support cell attachment and improved proliferation of AD-MSCs. Higher ALP activity and the appearance of more mineralized nodules on the collagen/P-PCL scaffold than in other test groups were concrete proof of the osteoinductivity of this scaffold. Moreover, real-time PCR analyses confirmed that the collagen/P-PCL scaffold was able to induce the AD-MSCs toward osteogenic differentiation. The results suggested that a biodegradable collagen/P-PCL scaffold holds potential for bone regeneration applications.